Digital technostress and self-efficacy: Predicting generation z’s intention to use online mutual fund platforms in Indonesia - Santi Putriani; Dewita Puspawati (Journal of Innovation in Business and Economics, 2026)
This study investigates the effects of technostress and digital technology self-efficacy on Generation Z investors’ intention to use online mutual fund platforms in Indonesia. A quantitative survey was conducted among users of Bibit, Tanamduit, and Ajaib, and the data were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings reveal that digital overload significantly reduces the intention to use online mutual funds, whereas higher digital technology self-efficacy enhances usage intention and mitigates the adverse effects of technostress. These results suggest that technostress is not solely detrimental but can be managed through users’ coping resources. Practical implications highlight the need for simplified interface design, personalized information filters, and digital literacy initiatives to strengthen user confidence and engagement in fintech investment platforms.